Air‐Blown Entrained‐Flow Gasification of Biocoal from Hydrothermal Carbonization. Issue 2 (30th November 2016) - Briesemeister, Ludwig; Kremling, Michael; Fendt, Sebastian; Spliethoff, Hartmut
Abstract: Hydrothermal carbonization was used to convert green waste into a high‐quality biocoal that was applied to an air‐blown entrained‐flow gasifier. Fuel‐specific operating parameters are required to achieve complete fuel conversion and operate the gasifier at high efficiency. Therefore, different air‐to‐fuel equivalence ratios and steam addition were applied to investigate effects on gasifier performance. Fuel and carbon conversion were determined by char‐particle analysis. The syngas composition and cold gas efficiencies were determined and the solid‐phase adsorption method was used for tar measurements. It was shown that owing to high conversion rates and comparably low tar loading, biocoal is very applicable for entrained‐flow gasification. Higher gas preheating temperatures would improve the process. Abstract : Gasification is a promising technology for energy generation from biomass. Entrained‐flow gasification has been applied on biocoal made from green waste by using hydrothermal carbonization. Stoichiometry and steam addition were varied to see the influence on the gasifier performance. Fuel conversion, carbon conversion, and cold gas efficiency were determined. Tar loading of the syngas was measured.